Into the unknown : the quest to understand the mysteries of the cosmos - Johnson, Kelsey (Basic Books, 2024)
"Humans have learned a lot about the world around us and the universe beyond. We have had powerful insights and created profound theories about the universe and everything in it. Surely the ultimate theory must be waiting, just beyond our current knowledge. Well, maybe. In Into the Unknown, astrophysicist Kelsey Johnson takes us to the edge of scientific understanding about the universe: What caused the Big Bang? What happens inside black holes? Are there other dimensions? She doesn't just celebrate what we know but rather what we don't, and asks what it means if we never find that knowledge. Exploring the convergence of science, philosophy, and theology, Johnson argues we must reckon with possibilities-including those that may be beyond human comprehension. The very places where we run smack into total ignorance are the places where the most important questions-about the philosophy of knowledge, the nature of our cosmos, and even the existence of God-await. As accessible as it is profound, Into the Unknown invites each of us to join in the great quest for knowledge"--